(untitled) (Bangladesh Journal of Zoology, 2010)
A total of 11 species under five different genera was collected from November 1997 to October 1998 from the two locations of Chittagong, viz. Chittagong University campus and Chittagong Metropolitan city representing rural and urban environment, respectively. The mosquito species were: Aedes albopictus, Ae. aegypti, Culex quinquefasciatus, Cx. mimulus, Cx. hutchinsoni, Cx. vishnui, Anopheles kochi, An. barbirostris, Mansonia annulifera, Mn. uniformis and Armigeres subalbatus. Ae. aegypti was the most predominant species in the urban area of Chittagong city, while in the rural environment of Chittagong University campus Ae. albopictus appeared to be the pre-dominant. Ae. albopictus was 63.2% among the total indoor day-resting adult mosquitoes in CU campus, whereas in the city in similar collection, Ae. aegypti was predominant with 50% of the total population. In CU campus the other mosquitoes in this type of collection formed 36.8% of the total mosquitoes; on the other hand in Chittagong city the collection was 50%. The number of Ae. albopictus and Ae. aegypti collected per man hour were 16.9 and 10.8, respectively. Bangladesh J. Zool. 38(1): 23-29, 2010